2019
DOI: 10.3390/ijms20061455
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophosphatase MK-STYX Alters Histone Deacetylase 6 Cytoplasmic Localization, Decreases Its Phosphorylation, and Increases Detyrosination of Tubulin

Abstract: The catalytically inactive mitogen-activated protein (MAP) kinase phosphatase, MK-STYX (MAPK (mitogen-activated protein kinase) phosphoserine/threonine/tyrosine-binding protein) interacts with the stress granule nucleator G3BP-1 (Ras-GAP (GTPase-activating protein) SH3 (Src homology 3) domain-binding protein-1), and decreases stress granule (stalled mRNA) formation. Histone deacetylase isoform 6 (HDAC6) also binds G3BP-1 and serves as a major component of stress granules. The discovery that MK-STYX and HDAC6 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 59 publications
(130 reference statements)
0
14
0
Order By: Relevance
“…We found that HDAC6 localizes in both the cytosol and nucleus in the presence of MK‐STYX, instead of solely in the cytosol (Fig. 3A) [67]. In addition, HDAC6 phosphorylation at Ser 22 decreases in the presence of MK‐STYX (Fig.…”
Section: Mk‐styx Promotes Dephosphorylation Of Histone Deacetylasementioning
confidence: 99%
See 1 more Smart Citation
“…We found that HDAC6 localizes in both the cytosol and nucleus in the presence of MK‐STYX, instead of solely in the cytosol (Fig. 3A) [67]. In addition, HDAC6 phosphorylation at Ser 22 decreases in the presence of MK‐STYX (Fig.…”
Section: Mk‐styx Promotes Dephosphorylation Of Histone Deacetylasementioning
confidence: 99%
“…In addition, HDAC6 phosphorylation at Ser 22 decreases in the presence of MK‐STYX (Fig. 3B) [67], illustrating that MK‐STYX influences HDAC6 dynamics in both its subcellular localization and post‐translational modification [67]. Thus, a strong link for the role of MK‐STYX in HDAC6 signaling has been established, and MK‐STYX as a regulator in the stress response pathway has been further supported, but how MK‐STYX inhibits stress granules remains elusive.…”
Section: Mk‐styx Promotes Dephosphorylation Of Histone Deacetylasementioning
confidence: 99%
“…How intracellular signaling affects HDAC6 is of paramount importance in order to implement effective approaches that modulate HDAC6 and intracellular transport. Cao et al [ 90 ] showed that MAPK (mitogen-activated protein kinase) regulates HDAC6 localization and phosphorylation, in addition to having positive effects on tyrosinated tubulin and microtubule (MT) stability.…”
Section: Intracellular Transport and Neurodegenerationmentioning
confidence: 99%
“…The catalytically inactive MAP kinase phosphatase (MK-STYX) interacts with the stress granule nucleator G3BP-1 to decrease stress granule formation. Since MK-STYX is a signaling molecule along HDAC6 activity, future studies should explore in more detail the relationship between HDAC6i and stress granule regulation [ 90 ].…”
Section: Aggregates and Neurodegenerationmentioning
confidence: 99%
“…Circulating tumor cells play a major role in tumor dissemination and metastasis, and Wu et al reported the enrichment in nuclear localized DUSP6 in circulating tumor cells from triple negative breast cancers, as well as in brain metastases, suggesting a specific role for nuclear DUSP6 in cancer spreading [21]. Finally, Cao et al provided new insights into the functions of the catalytically inactive MK-STYX pseudophosphatase as an indirect regulator of post-translational modifications from proteins regulating microtubule dynamics, including histone deacetylase isoform 6 and tubulin [22].…”
mentioning
confidence: 99%